PASSIVE AND ACTIVE SOLAR ENERGY FOR NET ZERO ENERGY BUILDING (NZEB) IN ALGERIA CASE STUDY: SOLAR HOUSE OF BOUSSAÂDA - Sotehi, O.; Chaker, A. (Journal of Fundamental and Applied Sciences, 2019)
The aim of our work is to conduct a study on the use of active and passive solar energy in the building sector for obtaining a net zero energy building. A solar house of the solar village built in Boussaâda is chosen to carry out simulation calculations in three different climates of Algeria (Algiers, Constantine and Ouargla). The passive system simulation results show that the use of these devices, such as Trombe walls and glazed surfaces, allows significant energy savings (although considered insufficient). A reduction in heating needs of 2.12, 1.7 and 2.64 times respectively for the cities of Algiers, Constantine and Ouargla is obtained. Improving the thermal performance of the structure could lead to a greater reduction in heating and cooling requirements. The reduction is estimated at 38.48, 30.44 and 21.49 % respectively for the cities of Algiers, Constantine and Ouargla. The use of active solar systems allows covering energy needs of the solar house. High solar fractions of DHW are obtained. The electrical energy produced can cover the extra needs of DHW, HVAC, lighting and household equipment’s. Net Zero Building Energy (nZEB) can be obtained for different climates in Algeria.